2015
DOI: 10.1016/j.jaci.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The alpha-gal story: Lessons learned from connecting the dots

Abstract: Anaphylaxis is a severe allergic reaction that can be rapidly progressing and fatal; thus, establishing the etiology of anaphylaxis is pivotal to long-term risk management. Our recent work has identified a novel IgE antibody response to a mammalian oligosaccharide epitope, galactosealpha-1,3-galactose (alpha-gal). IgE to alpha-gal has been associated with two distinct forms of anaphylaxis: i) immediate onset anaphylaxis during first exposure to intravenous cetuximab, and ii) delayed onset anaphylaxis 3-6 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…A detailed chronology of scientific discoveries about AGS starts in 1989, when Mrs. Sandra Latimer and Dr. Antony Deutsch ( 9 ) reported in Georgia (USA) the first case reports of delayed red meat allergy with a possible correlation to tick bites. In 2007, Van Nunen et al ( 10 ) reported an Australian case series of delayed red meat allergy, with patients recalling I. holocyclus tick bites before symptom onset and having positive prick test or specific IgE to red meat.…”
Section: From the First Case Reports To Sensitization And Clinical Manifestationsmentioning
confidence: 99%
“…A detailed chronology of scientific discoveries about AGS starts in 1989, when Mrs. Sandra Latimer and Dr. Antony Deutsch ( 9 ) reported in Georgia (USA) the first case reports of delayed red meat allergy with a possible correlation to tick bites. In 2007, Van Nunen et al ( 10 ) reported an Australian case series of delayed red meat allergy, with patients recalling I. holocyclus tick bites before symptom onset and having positive prick test or specific IgE to red meat.…”
Section: From the First Case Reports To Sensitization And Clinical Manifestationsmentioning
confidence: 99%